Gestão colaborativa e gestão de risco: um estudo sobre capacidades complementares (Management and Connections Journal, 2020)
Collaborative management (CMSC) can complement risk management (RMSC) and contribute to risk mitigation that compromise the supply chain flow (SC). It is the intention of the research to analyze through the literature and a practical study in a SC of organizations of ​​food-service, whether this statement can be substantiated. It was searched 13 companies, one Logistic Provider (LP), 4 clients of the operator, and 8 other suppliers. With the analysis of the literature the research suggests points of convergence between the themes, and establishes 5 propositions that were evaluated through the field research with 34 professionals. Data analysis, in the first stage, makes use of descriptive statistics by evaluate the interviewees and the companies to adopt or not the collaborative management, in the second, the paired statistical test is used, which applies when the data are related according to some criterion that introduces a marked influence. The study contributes to a better understanding of possible complementarities between the two themes. It is possible to state, with exception to the issues related to losses, that SCRM falls within the scope of the SCCM. This, incorporates points related to mitigation and the existing uncertainties, and the competitive advantage obtained, contributing to risk management.